Assessment of Cutting Technology Above Seabed for Cost Reduction Purpose - Nor Salim, Nor Zafry (Universiti Teknologi PETRONAS, 2017)
At the end of offshore structure design life, decommissioning offshore platform should be execute as one of the legislative requirement in offshore installation. Malaysia decommissioning activities increasing as the number of offshore platform reach their design life approximately about 360 platforms. The execution of offshore decommissioning need to be properly planned as the risk is huge due to the lack of expert in decommissioning field. Decommissioning cost has taken into consideration in project planning to increase the profit gain by the operator. The scope of this paper is to propose cutting technology above sea bed for cost reduction purpose. Selection of cutting technology is important to reduce the cost element involve in jacket removal. Diamond wire saw, Abrasive Water Jet and Diver Torch are selected for the nonexplosive cutting method technology. In order to get the best cutting technology, study of Qualitative analysis on the selected technologies based on the safety, technical, cost and environmental impact are done. The factors are measured by indicating score of each technology and ranked. Indirect cost of the technologies calculated and compared which the cheapest cost is Diamond Wire Saw.